Green Synthesis of AgNPs Stabilized with biowaste and their antimicrobial activities - Jasuja,Nakuleshwar Dut (2014)
In the present study, rapid reduction and stabilization of Ag+ ions with different NaOH molar concentration (0.5 mM, 1.0 mM and 1.5 mM) has been carried out in the aqueous solution of silver nitrate by the bio waste peel extract of P.granatum. Generally, chemical methods used for the synthesis of AgNPs are quite toxic, flammable and have adverse effect in medical application but green synthesis is a better option due to eco-friendliness, non-toxicity and safe for human. Stable AgNPs were synthesized by treating 90 mL aqueous solution of 2 mM AgNO3 with the 5 mL plant peels extract (0.4% w/v) at different NaOH concentration (5 mL). The synthesized AgNPs were characterized by UV-Vis spectroscopy, TEM and SEM. Further, antimicrobial activities of AgNPs were performed on Gram positive i.e. Staphylococcus aureus, Bacillus subtilius and Gram negative i.e. E. coli, Pseudomonas aeruginosa bacteria. The AgNPs synthesized at 1.5 mM NaOH concentration had shown maximum zone of inhibition (ZOI) i.e. 49 ± 0.64 in E. coli, whereas Pseudomonas aeruginosa, Staphylococcus aureus and Bacillus subtilius had shown 40 ± 0.29 mm, 28 ± 0.13 and 42 ± 0.49 mm ZOI respectively. The MIC value of 30 g/mL observed for E. coli Whereas, Staphylococcus aureus, Bacillus subtilius and Pseudomonas aeruginosa had shown 45 µg/mL, 38 µg/mL, 35 µg/mL respectively. The study revealed that AgNPs had shown significant antimicrobial activity as compared to Streptomycin.